Vesayetten siyasete Türkiye’de sendikacılık : parti-devlet ilişkileri (1946-1967) - Çelik, Aziz (My University, 2009)
VESAYETTEN SİYASETE TÜRKİYE’DE SENDİKACILIK: PARTİ-DEVLET İLİŞKİLERİ (1946-1967) Bu çalışma 1946-1967 döneminde Türkiye’de sendikacılık, siyaset ve devlet ilişkilerini irdelemeyi amaçlamaktadır. Çalışma, sınıf oluşumunun önemli bir aşaması ve boyutu olan sendikacılık-siyaset-devlet ilişkilerinin Türkiye’deki gelişimine, özelliklerine ve sorun alanlarına ilişkin bir arayış ve anlama denemesidir. Çalışmada Türkiye’de sendikacılığın paternalist-partikülarist evreden, siyasallaşmaya ve sınıfsal davranış evresine yöneliminin öyküsü ele alınmaktadır. Tezde 1946 sendikacılığından 1967 yılında Türk-İş’in bölünmesi ve DİSK’in kuruluşuna kadar olan dönem irdelenmektedir. Kısa süren bağımsız 1946 sendikacılığın ardından 1947’de başlayan ve 1960’a kadar devam eden dönem vesayet sendikacılığının inşası olarak ele alınmaktadır. Bu dönemde sendikalar ağır bir baskı ve vesayet altındadır ve siyasal katılımları engellenmiştir. 1960-1967 dönemi ise siyasallaşma, siyasal katılım ve partileşme arayışlarının ön plana çıktığı bir dönemdir. Bu dönemde sendikal hareket vesayetten kurtulma arayışlarına girmiştir. Bir yandan lobicilik ve baskı grubu eğilimleri, öte yandan işçi partisi arayışları gündeme gelmiştir. Sendika-siyaset ilişkileri konusunda yaşanan farklılaşma sendikal harekette ciddi bir bölünmeye yol açmış ve DİSK kurulmuştur. Çalışmada birincil kaynaklar (ulusal ve uluslararası arşiv belgeleri) ile dönemin tanıklarıyla yapılan ayrıntılı görüşmeler önemli bir tutmaktadır. emek, emek tarihi, sendikacılık, sendikalar ve siyaset, Türkiye sendikal hareketi

THE TRADE UNIONISM IN TURKEY FROM PATERNALISM TO POLITICAL PARTICIPATION: RELATIONS WITH POLITICAL PARTIES AND THE STATE (1946-1967) This study aims to analyse relations between the trade union movement, politics and the state in the period of 1946-1967 in Turkey. It is an effort to understand and explore the evolution process, specifications and problem areas of the relations between trade unionism, politics and the state which constitute a critical stage and dimension of the class formation in Turkey. We try to tell the story of the evolution of the trade unionism of Turkey from paternalistic-particularistic period to the period of political participation (or politicization) and class-consciousness. In the study, the period from the trade unionism of 1946 to the establishment of Turk-Is Confederation and then to the founding of the progressive confederation DISK are explored. Following the short period of independent and autonomous 1946 unionism, the paternalistic unionism was created from 1947 until 1960. In this period, trade unions were under heavy pressure by the government and their political participation was blocked/ prohibited by the state. Within the period between 1960 and 1967, trade unions were in search for depaternalization, politicization and political participation of the labor movement. The organization of a labour party was a result of that kind of searching. In order to solve the labour problems, on the one hand lobbying and acting as a pressure group, on the other hand class based approaches and labour party initiatives emerged. The differences within trade union movement on how to intervene in politics resulted in the establishment of a new national trade union confederation. In the formation of this study, primary sources (national and foreign archival documents and detailed interviews with the people of the period) played a critical role. Key words: labour, labour history, trade unionism, trade unions and politics, Turkish trade union movement
Keywords: Çalışma Ekonomisi; Sendikacılık; Siyaset ve Yönetim_Sendikalar